Surface Design Exploration to Diversify Ciwaringin Cirebon Batik Design - JOHN MARTONO; EKA ARIFIANTY PUSPITA (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2023)
Diversification has been recognized as effective in developing commercial enterprises. However, this strategy requires the commercial business to deeply understand its basic competencies and be aware of changing market trends. In the efforts to develop Ciwaringin batik SMEs, the diversification plan necessitates the Ciwaringin batik SMEs revisiting their unique competencies, namely the hand-writing batik process and the popular trend in 2022/2033, particularly the rising consumption of home décor and hypernature themes. As a result, implementing a diversification strategy in Ciwaringin batik SMEs requires investigating opportunities for developing Ciwaringin batik designs that are unique in their written batik techniques through surface design exploration in order to be responsive to the hypernature-themed home décor trend. Exploration of surface design on textiles was carried out to develop the appearance of Ciwaringin hand-writting batik so that it is relevant to the changing home decor market trends, namely the organic and textured appearances of the hypernature theme. The surface design exploration process is equipped with a data analysis to implement appropriate surface design exploration that supports the Ciwaringin batik diversification strategy. The creative method that combines data analysis and surface design exploration produced several Ciwaringin hand-writing batik designs that display the quality of the organic textured textile surfaces with bright colors typical of the hypernature theme. The Ciwaringin batik designs from surface design exploration are also designed to be home décor items, namely aesthetic wall elements that beautify a residential space.